Influence of passage number on the impact of the secretome of adipose tissue stem cells on neural survival, neurodifferentiation and axonal growth - Serra, Sofia Cravino (2018)
Mesenchymal stem cells (MSCs), and within them adipose tissue derived stem cells (ASCs), have been shown to have therapeutic effects on central nervous system (CNS) cell populations. Such effects have been mostly attributed to soluble factors, as well as vesicles, present in their secretome. Yet, little is known about the impact that MSC passaging might have in the secretion therapeutic profile. Our aim was to show how human ASCs (hASCs) passage number influences the effect of their secretome in neuronal survival, differentiation and axonal growth. For this purpose, post-natal rat hippocampal primary cultures, human neural progenitor cell (hNPCs) cultures and dorsal root ganglia (DRGs) explants were incubated with secretome, collected as conditioned media (CM), obtained from hASCs in P3, P6, P9 and P12. Results showed no differences when comparing percentages of MAP-2 positive cells (a mature neuronal marker) in neuronal cultures or hNPCs, after incubation with hASCs secretome from different passages. The same was observed regarding DRG neurite outgrowth. In order to characterize the secretomes obtained from different passages, a proteomic analysis was performed, revealing that its composition did not vary significantly with passage number P3 to P12. Results allowed us to identify several key proteins, such as pigment epithelium derived factor (PEDF), DJ-1, interleucin-6 (IL-6) and galectin, all of which have already proven to play neuroprotective and neurodifferentiating roles. Proteins that promote neurite outgrowth were also found present, such as semaphorin 7A and glypican-1. We conclude that cellular passaging does not influence significantly hASCs's secretome properties especially their ability to support post-natal neuronal survival, induce neurodifferentiation and promote axonal growth.